Deep reinforcement learning for scheduling in large-scale networked control systems - Redder, Adrian; Ramaswamy, Arunselvan; Quevedo, Daniel (Proceedings of the 8th IFAC Workshop on Distributed Estimation and Control in Networked Systems)
This work considers the problem of control and resource allocation in networked systems. To this end, we present DIRA a Deep reinforcement learning based Iterative Resource Allocation algorithm, which is scalable and control-aware. Our algorithm is tailored towards large-scale problems where control and scheduling need to act jointly to optimize performance. DIRA can be used to schedule general time-domain optimization based controllers. In the present work, we focus on control designs based on suitably adapted linear quadratic regulators. We apply our algorithm to networked systems with correlated fading communication channels. Our simulations show that DIRA scales well to large scheduling problems.
Keywords: Networked control systems; deep reinforcement learning; large-scale systems; resource scheduling; stochastic control

Mapping Value in Business Markets: An Integrative Framework - Eggert, Andreas; Kleinaltenkamp, Michael; Kashyap, Vishal (Industrial Marketing Management)

Exploring the link between payment schemes and customer fraud: a mental accounting perspective - Garnefeld, Ina; Eggert, Andreas; Husemann-Kopetzky, Markus; Boehm, Eva (Journal of the Academy of Marketing Science)

Service Growth by Acquisition – An Event Study - Eggert, Andreas; Boehm, Eva; Akalan, Rodi; Gebauer, Heiko

Gift Purchases as Catalysts for Strengthening Customer–Brand Relationships - Eggert, Andreas; Steinhoff, Lena; Witte, Carina (Journal of Marketing)

Intelligente Herstellung zuverlässiger Kupferbondverbindungen - Sextro, Walter; Brökelmann, Michael
Dieses Buch beschreibt basierend auf dem gleichnamigen Innovationsprojekt im Spitzencluster it’s OWL die Entwicklung intelligenter Verfahren und Systeme, um auch unter variablen Produktionsbedingungen eine zuverlässige Massenfertigung von Kupferbondverbindungen sicherzustellen.Dabei wird der gesamte Prozess der Ultraschall-Verbindungsbildung modelliert. Dies beinhaltet u. a. ein Reibmodell mit gekoppeltem Anbindungsmodell, den Ultraschall-Erweichungseffekt und den Verschleiß des Bondwerkzeugs. Zudem wird das Konzept einer selbstoptimierenden Bondmaschine vorgestellt, welche Prozessparameter in Abhängigkeit von Störgrößen wie Verschleiß anpasst.Das Ultraschallbonden mit Aluminiumdraht ist ein etabliertes Fertigungsverfahren zur Kontaktierung von Leistungshalbleitern. Zukünftige Leistungshalbleiterchips erfordern jedoch einen Technologiewechsel zu Kupferdraht. Die Prozessparameter unterscheiden sich dabei deutlich von den bekannten Aluminiumprozessen, ihre Wechselwirkungen sind weitestgehend unbekannt.
Keywords: Abschlussbericht zum Spitzenclusterprojekt InCuB

Editorial - Fränzle, Martin; Kapur, Deepak; Wehrheim, Heike; Zhan, Naijun (Formal Asp. Comput.)

Störeffektunterdrückung in 2D-Messdaten mittels DiscoGAN - Johannesmann, Sarah; Springer, Dimitri; Thiel, Christian; Henning, Bernd (Fortschritte der Akustik - DAGA 2019)

Data Independence for Software Transactional Memory - König, Jürgen; Wehrheim, Heike (NASA Formal Methods - 11th International Symposium, NFM 2019, Houston, TX, USA, May 7-9, 2019, Proceedings)

Verifying C11 programs operationally - Doherty, Simon; Dongol, Brijesh; Wehrheim, Heike; Derrick, John (Proceedings of the 24th ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming, PPoPP 2019, Washington, DC, USA, February 16-20, 2019)

Combining Verifiers in Conditional Model Checking via Reducers - Beyer, Dirk; Jakobs, Marie-Christine; Lemberger, Thomas; Wehrheim, Heike (Software Engineering and Software Management (SE/SWM 2019), Stuttgart, Germany, February 18-22, 2019)

Testing Balancedness of ML Algorithms - Sharma, Arnab; Wehrheim, Heike (Software Engineering and Software Management, {SE/SWM} 2019, Stuttgart, Germany, February 18-22, 2019)

PeSCo: Predicting Sequential Combinations of Verifiers - (Competition Contribution) - Richter, Cedric; Wehrheim, Heike (Tools and Algorithms for the Construction and Analysis of Systems - 25 Years of {TACAS:} TOOLympics, Held as Part of ETAPS 2019, Prague, Czech Republic, April 6-11, 2019, Proceedings, Part III)

Verification Artifacts in Cooperative Verification: Survey and Unifying Component Framework - Beyer, Dirk; Wehrheim, Heike (CoRR)

Who trades cryptocurrencies, how do they trade it, and how do they perform? Evidence from brokerage accounts - Hasso, Tim; Pelster, Matthias; Breitmayer, Bastian (Journal of Behavioral and Experimental Finance)
We investigate the demographic characteristics, trading patterns, and performance of 465.926 brokerage accounts with respect to cryptocurrency trading. We find that cryptocurrency trading became increasingly popular across individuals of all different groups of age, gender, and trading patterns. Yet, men are more likely to engage in cryptocurrency trading, trade more frequently, and more speculative, respectively. As a result, men realize lower returns. Furthermore, we find that investors vary their trading patterns across different asset classes.
Keywords: Cryptocurrencies Bitcoin Trading Investor returns Demographics

Analyzing Data Usage in Array Programs - Haltermann, Jan

Akustische Charakterisierung der mechanischen Eigenschaften künstlich gealterter Polymere - Webersen, Manuel; Hüttner, Matthias; Woitschek, Fabian; Moritzer, Elmar; Henning, Bernd (Fortschritte der Akustik - DAGA 2019)

Automating Multi-Label Classification Extending ML-Plan - Wever, Marcel Dominik; Mohr, Felix; Tornede, Alexander; Hüllermeier, Eyke
Existing tools for automated machine learning, such as Auto-WEKA, TPOT, auto-sklearn, and more recently ML-Plan, have shown impressive results for the tasks of single-label classification and regression. Yet, there is only little work on other types of machine learning problems so far. In particular, there is almost no work on automating the engineering of machine learning solutions for multi-label classification (MLC). We show how the scope of ML-Plan, an AutoML-tool for multi-class classification, can be extended towards MLC using MEKA, which is a multi-label extension of the well-known Java library WEKA. The resulting approach recursively refines MEKA's multi-label classifiers, nesting other multi-label classifiers for meta algorithms and single-label classifiers provided by WEKA as base learners. In our evaluation, we find that the proposed approach yields strong results and performs significantly better than a set of baselines we compare with.

Konstruktion und Zustandsüberwachung eines Gummi-Metall-Teils mit integriertem Thermoelement - Bender, Amelie; Reinke, Kai; Sextro, Walter (10. VDI-Fachtagung Schwingungen von Windenergieanlagen 2019)
Gummi-Metall-Teile (GM-Teile) werden zur Schwingungsreduktion u. a. in Windenergieanlagen eingesetzt. Mögliche Anwendungen der Teile liegen in Wellen-, Generator- und Getriebelagerungen, Lagern für die Gondel und ihre Komponenten sowie in Drehmomentstützen. Mit dem Ziel eine prädiktive Instandhaltung zu realisieren, soll eine Zustandsüberwachung für die GM-Teile entwickelt werden. Diese Entwicklung basiert auf der Umsetzung diverser Schritte. Neben der funktionalen Betrachtung wird zwingend auch die konstruktive Integration der Sensoren in das überwachte Teil berücksichtigt. Der Schwerpunkt dieser Arbeit liegt auf der verwendeten Messgröße Temperatur, die mittels ausgewählter Sensorik detektiert wird. Dabei werden Lebensdauerversuche unter instationären Betriebsbedingungen durchgeführt, um diese Messdaten zu generieren. In der Datenauswertung werden sie hinsichtlich der Degradierung des GM-Teils analysiert und für die Ermittlung der nutzbaren Restlebensdauer verwendet. Rubber-metal-elements are used for isolation of vibrations e. g. in wind turbines. Possible applications of the elements are shaft bearings, generator bearings, gearbox bearings, bearings for the nacelle and its components and torque supports. In order to realize predictive maintenance, an accurate condition monitoring system for rubber-metal-elements should be developed. During that development different aspects have to be implemented. Additionally to the functional analysis, the constructive integration of the sensors into the monitored part is mandatory. The focus of this work is on the measured variable temperature, which is detected by means of appropriate sensors. Thereby lifetime tests are run under non-stationary operating conditions to generate temperature measurements. During data analysis, the measured data is analyzed regarding the degradation of the rubber-metal-elements and remaining useful lifetimes are estimated.

Integration von Verlässlichkeitsmodellen der Entwicklung in einen Digitalen Zwilling zur Umsetzung einer vorausschauenden Instandhaltung - Kaul, Thorben; Hentze, Julian; Sextro, Walter; Gräßler, Iris (Fachtagung Mechatronik 2019 Paderborn)
In der Entwicklung mechatronischer Systeme spielt die Steigerung der Verlässlichkeit und somit auch der Zuverlässigkeit und der funktionalen Sicherheit eine entscheidende Rolle. Die modellbasierte Entwicklung liefert in Kombination mit unterstützender Software einen wichtigen Beitrag zur Absicherung der Verlässlichkeit mechatronischer Systeme in frühen Entwicklungsphasen. In der Nutzungsphase ermöglichen aktuelle Verfahren der Zustandsüberwachung und moderne Methoden der Regelungstechnik eine effektive Absicherung. Modelle aus der Entwicklung mechatronischer Systeme enthalten weitreichende Informationen über die Architektur, das Verhalten und die Verlässlichkeit eines Systems. Diese Modelle können als Grundlage für die Erstellung eines Digitalen Zwillings für die vorausschauende Instandhaltung verwendet und mit Zustandsdaten des realen Systems kombiniert werden. Die Nutzung der Modelle für den Digitalen Zwilling bietet weitreichende Potenziale und vereinfacht dessen Erzeugung. Die Veröffentlichung beschreibt Rahmenbedingungen der Integration und stellt die Potenziale des Digitalen Zwillings zur vorausschauenden Instandhaltung dar.